Multiple drug resistance in salmonellae in England and Wales: a comparison between 1981 and 1988. Issue 7 (July 1990) - Ward, L R; Threlfall, E J; Rowe, B
Abstract : Each year from 1981 through to 1988 the most common serotypes isolated from man in England and Wales and identified at the Division of Enteric Pathogens were S typhimurium, S enteritidis, and S virchow. In 1981 these three serotypes accounted for 45%, 12%, and 7% of isolations. The remaining 35% comprised strains belonging to a further 188 different serotypes, none of which accounted for more than 1% of the total. In 1988 S typhimurium accounted for 24% of isolations, S enteritidis 57%, and S virchow 4%. The remaining 15% comprised strains of a further 184 serotypes. The resistances to the common antimicrobial drugs in non-typhoidal salmonellas isolated in England and Wales in 1981 and 1988 were reported with particular reference to resistance to four or more antimicrobial drugs (multiple resistance). For S typhimurium the overall percentage of resistant strains varied little, but multiple resistance more than doubled from 5% to 12%; in S enteritidis the incidence remained the same. In S virchow the percentages of strains resistant to all the antimicrobial drugs and in particular, to chloramphenicol, streptomycin, trimethoprim and furazolidone, rose from 0.2% to 10.4%. Salmonella enteritis in man is usually a self limiting disease and antimicrobial treatment is seldom required; but should spread beyond the intestine occur, effective antimicrobial treatment is essential. Under these circumstances a knowledge of the likelihood of resistances to commonly available drugs could be of considerable value to the clinician.